2021
DOI: 10.1001/jamainternmed.2020.8250
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Intensity of Diagnostic Evaluation With Outcomes in Incidentally Detected Lung Nodules

Abstract: IMPORTANCE Whether guideline-concordant lung nodule evaluations lead to better outcomes remains unknown.OBJECTIVE To examine the association between the intensity of lung nodule diagnostic evaluations and outcomes, safety, and health expenditures. DESIGN, SETTING, AND PARTICIPANTSThis comparative effectiveness research study analyzed health plan enrollees at Kaiser Permanente Washington in Seattle, Washington, and Marshfield Clinic in Marshfield, Wisconsin, with an incidental lung nodule detected between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…17 This study also demonstrated a 3-year overall survival (OS) rate of 63.6% versus 30.3% for symptomatic cancers and this is supported by another study, 18 which confirmed a median OS benefit of 38.9 months versus 16.1 months. However in contrast, recent evidence has suggested 19 that intensive diagnostic evaluation of pulmonary nodules is associated with greater procedural complications and unnecessary radiation exposure with little benefit. Certainly, in the retrospective audit five patients with indeterminate nodules were advised to have a six-month follow-up CT scan to determine any changes and to exclude a small lung malignancy.…”
Section: Discussionmentioning
confidence: 94%
“…17 This study also demonstrated a 3-year overall survival (OS) rate of 63.6% versus 30.3% for symptomatic cancers and this is supported by another study, 18 which confirmed a median OS benefit of 38.9 months versus 16.1 months. However in contrast, recent evidence has suggested 19 that intensive diagnostic evaluation of pulmonary nodules is associated with greater procedural complications and unnecessary radiation exposure with little benefit. Certainly, in the retrospective audit five patients with indeterminate nodules were advised to have a six-month follow-up CT scan to determine any changes and to exclude a small lung malignancy.…”
Section: Discussionmentioning
confidence: 94%
“…In this retrospective cohort study, we found that almost 1 in 3 patients received unnecessary lung cancer screening, and the rate dramatically varied by different characteristics. Previous study suggested the disadvantage of unnecessary Chest CT, and there were studies about overuse of Chest CT in patients with breast cancer or studies about lung cancer screening inconsistent with USPSTF, [16][17][18] but to our knowledge, this is the rst study to assess the overuse of Chest CT during follow-up after nding nodules suspicious for lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…There is no clinical or radiological feature that definitively identifies malignant SPNs, and SPNs often require endobronchial or transthoracic tissue biopsy to rule out malignancy [2,4]. For small, peripheral, or sub-solid nodules, the diagnostic yield of biopsies is low, leading to patient anxiety, increased healthcare costs, additional procedures, and prolonged radiographic surveillance [4][5][6].…”
Section: Introductionmentioning
confidence: 99%